CULTURE OF OBTAINING POLITICAL INFORMATION IN AN INFORMED SOCIETY - Abror Xaydarov (Web of Journals Publishing, 2025)
The article analyzes the problems of information culture at the current stage of development of society, the mechanisms of influence of education, mass media and communications on the culture of receiving political information.
Keywords: Information, information society, information culture, political security, political culture, Internet, means of dissemination of information, political socialization.